De-escalation versus standard dual antiplatelet therapy in patients undergoing percutaneous coronary intervention: a systematic review and meta-analysis. (2nd January 2020) - Guo, Chen; Li, Min; Lv, Yong-Hui; Zhang, Ming-Bo; Wang, Zhi-Lu
Abstract: Switching from a potent P2Y12 blocker to clopidogrel is not uncommon for antiplatelet therapy in patients undergoing percutaneous coronary intervention. This meta-analysis aimed to investigate the efficacy and safety of this de-escalation strategy. Medical literature databases were searched for analysis comparing continued potent antiplatelet therapy and switching to clopidogrel with no language restrictions from inception to 07/May/2018. The primary endpoints of major adverse cardiovascular events (MACE) and major bleeding together with additional efficacy outcomes were assessed by random-effects and fixed-effects meta-analysis. A total of 17 896 patients in 13 studies were eligible for analysis, while 17 579 (98.2%) patients presented as acute coronary syndrome and 4105 (23%) patients received the de-escalation therapy. Incidence of MACE was virtually identical in both de-escalation and standard potent antiplatelet therapy groups (odds ratio 0.91, 95% CI 0.73–1.14; P = 0.43). Insignificant difference was also observed in major bleeding (0.99, 0.62–1.60; P = 0.97), all-cause death (0.95, 0.61–1.46; P = 0.81), cardiovascular death (0.66, 0.31–1.42; P = 0.29), myocardial infarction (1.12, 0.80–1.58; P = 0.51), stent thrombosis (1.09, 0.50–2.36; P = 0.83), unplanned revascularization (1.09, 0.83–1.41; P = 0.54), and stroke (1.16, 0.62–2.19; P = 0.64). In conclusion, de-escalation of antiplatelet therapy is associated with nonsignificant differences in both ischemic events and major bleeding compared with standard potent antiplatelet therapy in patients undergoing percutaneous coronary intervention. The feasibility and even superiority of this strategy need to be elucidated by further randomized trials.